2017
DOI: 10.1038/s41598-017-00406-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Angiotensin II in Glomerular Volume Dynamics and Podocyte Calcium Handling

Abstract: Podocytes are becoming a primary focus of research efforts due to their association with progressive glomeruli damage in disease states. Loss of podocytes can occur as a result of excessive intracellular calcium influx, and we have previously shown that angiotensin II (Ang II) via canonical transient receptor potential 6 (TRPC6) channels caused increased intracellular Ca2+ flux in podocytes. We showed here with patch-clamp electrophysiology that Ang II activates TRPC channels; then using confocal calcium imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 62 publications
(63 reference statements)
5
36
1
Order By: Relevance
“…According to our previous findings, 25 podocytic TRPC6 is the channel that mainly contributes to changes in [Ca 2+ ] i in normal and pathologic conditions. Here, we tested the expression level of TPRC6 in the kidney cortex in normal and diabetic conditions; as summarized in Figure 3E, DKD development resulted in a significant increase in TRPC6 expression in both STZ-treated wild-type SS and SS Nox42/2 strains.…”
Section: Diabetes-induced Calcium Mishandling Is Attenuated In Ss Noxmentioning
confidence: 81%
See 2 more Smart Citations
“…According to our previous findings, 25 podocytic TRPC6 is the channel that mainly contributes to changes in [Ca 2+ ] i in normal and pathologic conditions. Here, we tested the expression level of TPRC6 in the kidney cortex in normal and diabetic conditions; as summarized in Figure 3E, DKD development resulted in a significant increase in TRPC6 expression in both STZ-treated wild-type SS and SS Nox42/2 strains.…”
Section: Diabetes-induced Calcium Mishandling Is Attenuated In Ss Noxmentioning
confidence: 81%
“…Isolation and basal podocyte intracellular calcium ([Ca 2+ ] i ) measurements in rats and mice were done as described previously. [25][26][27] Isolated decapsulated glomeruli were incubated with Fura-2TH, AM and Fluo-4, AM (5 mM; Thermo Fisher Scientific) for 40 minutes at room temperature. Calcium imaging was performed as previously described.…”
Section: Isolation Of Glomeruli and Calcium Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the conditions were changed to 37˚C (without γ-IFN) to induce cell differentiation into mature podocytes and cells were cultured for 10-14 days. Differentiated podocytes were then divided into five groups: Normal glucose (NG) group (5.6 mmol/l), high glucose (HG) group (30 mmol/l), high mannitol group (NG + mannitol 25 mmol/l), the valsartan (VAL) group (HG + the AngII receptor blocker VAR, 10 -5 mmol/l), and HS group [HG + the TRP channel inhibitor (35), SAR7334, 1 µM) cultured in 37˚C for 48 h.…”
Section: Glomerular Morphological Characteristicsmentioning
confidence: 99%
“…In contrast, Throssell and colleagues 11 found significant low molecular weight proteinuria in acidotic rats, implying a tubular origin. Recent data reveal that the integrity of the glomerular filter is crucially determined by the concerted actions of the cellular components of the glomerulus [12][13][14] , especially podocytes 15 , which appear to tightly regulate glomerular permeability. Moreover, several in vitro and in vivo studies have indicated that both extra-cellular acidemia and bicarbonate therapy can exacerbate intra-cellular acidosis 6,16 , conceivably leading to cellular dysfunction.…”
Section: Introductionmentioning
confidence: 99%